Immediate effects of hip mobilization with movement in patients with hip osteoarthritis: A randomised controlled trial. (April 2016) - Beselga, Carlos; Neto, Francisco; Alburquerque-Sendín, Francisco; Hall, Toby; Oliveira-Campelo, Natália
Abstract: Background: Mobilization with movement (MWM) has been shown to reduce pain, increase range of motion (ROM) and physical function in a range of different musculoskeletal disorders. Despite this evidence, there is a lack of studies evaluating the effects of MWM for hip osteoarthritis (OA). Objectives: To determine the immediate effects of MWM on pain, ROM and functional performance in patients with hip OA. Design: Randomized controlled trial with immediate follow-up. Method: Forty consenting patients (mean age 78 ± 6 years; 54% female) satisfied the eligibility criteria. All participants completed the study. Two forms of MWM techniques (n = 20) or a simulated MWM (sham) (n = 20) were applied. Primary outcomes: pain recorded by numerical rating scale (NRS). Secondary outcomes: hip flexion and internal rotation ROM, and physical performance (timed up and go, sit to stand, and 40 m self placed walk test) were assessed before and after the intervention. Results: For the MWM group, pain decreased by 2 points on the NRS, hip flexion increased by 12.2°, internal rotation by 4.4°, and functional tests were also improved with clinically relevant effects following the MWM. There were no significant changes in the sham group for any outcome variable. Conclusions: Pain, hip flexion ROM and physical performance immediately improved after the application of MWM in elderly patients suffering hip OA. The observed immediate changes were of clinical relevance. Future studies are required to determine the long-term effects of this intervention. Highlights: Immediate effects of hip MWM and placebo were evaluated in patients with hip OA. MWM decreased pain, improved ROM, and physical function greater than placebo. These results direct future studies to investigate long-term efficacy.